PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Yunitasari, Ika; Pernamasari, Rieke (Jurnal Riset Keuangan dan Akuntansi, 2023)
The objective of this research is to determine how company performance and good corporate governance (GCG) impact financial distress in manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. This study employs a quantitative approach. The subjects of this research are manufacturing companies listed on the Indonesia Stock Exchange. Multiple linear regression analysis is used. The research findings indicate that GCG, measured through the audit committee, independent board of commissioners, and board of directors, does not have an impact on financial distress. Conversely, company performance, measured by Return on Assets (ROA) and Debt Equity Ratio (DER), does impact financial distress. This might be due to the financial factors being more easily measurable and directly assessable when predicting a company's bankruptcy. Keywords: Good Corporate Governance, Firm Performance, Financial distress